The Longitudinal Relationship Between Self-Esteem, Life Satisfaction, and Depressive and Anxiety Symptoms Among Chinese Adolescents: Within- and Between-Person Effects - Zongqiao Han; Shuai Chen; Yan Zhou; Yanling Liu; Cheng Guo (Behavioral Sciences)
Adolescents are especially vulnerable to experiencing depression and anxiety. This longitudinal study, from within- and between-person perspectives, explores how self-esteem relates to depressive and anxiety symptoms in Chinese adolescents and identifies the mediating factors impacting this relationship. Data were collected from 1025 junior and high school students in Southwestern China at three points over an 18-month period. This study utilized both traditional and random-intercept cross-lagged panel models to understand the dynamic developmental relationships. The general occurrence of depressive and anxiety symptoms increased longitudinally, with a more pronounced upward trend among female students. Between-person level analyses indicated bidirectional associations among self-esteem, life satisfaction, and depressive and anxiety symptoms. Moreover, life satisfaction emerged as a significant mediator. At the within-person level, self-esteem uniquely predicted both life satisfaction and subsequent depressive and anxiety symptoms. This study clarifies the longitudinal interplay between these constructs. Self-esteem, which denotes internal self-assessments, and life satisfaction, which denotes external evaluations of life, both significantly buffer the emergence of depressive and anxiety symptoms.